Political aspects of practicing methodological critique - Banaszak, Sławomir (Methodological critique in the practice of knowledge creation, 2019)
The author focuses on the political nature of scientific critique. The author’s theses are inspired by the once-well-known text of Michał Kalecki, one of the most influential Polish economists in the history of the discipline, in which he argued that ideological premises often overcame objective, scientific thinking. Similarly, the classic of modern social sciences, Vilfredo Pareto, calls these false justifications, which replace theses based on real premises, derivations. Sławomir Banaszak attempts to show examples of ideology in social sciences, the necessity of undertaking discussions with adversaries, and the apparent and non-obvious nature of the review of scientific achievements. He asks questions, including those about methodological specialization in the social sciences and the methodology of scientific work. In his opinion, critique, including methodological critique, is in retreat and disappearing. For this reason, he proposes indicators of the “criticality” of the discipline that may show off dominant attitudes in a particular field of science.